Preservation of the Anterior Branch of the Great Auricular Nerve during Benign Parotid Neoplasm Excision - Khalid B. Alghamdi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to examine the impact of the process of preservation of both divisions of great auricular nerve on patients' quality of life. This is a retrospective study conducted at King Abdulaziz University Hospital after receiving formal consent from the research ethics committee. For the analysis, charts of all patients who underwent partial parotidectomies (superficial parotidectomies) for benign neoplasm were evaluated and the results were validated. A total 45 cases of superficial parotidectomies were observed, out of which, 15 had preservation of the great auricular nerve (anterior and posterior divisions), and numbness and feeling of well-being were better in this group as compared to the great auricular nerve anterior division sacrifice group. The influence of great auricular nerve sacrifice morbidity on patient’s quality of life varied. Great auricular nerve morbidity requires further eff orts to be made in order to preserve the posterior and anterior branches of this nerve when possible and in the case of the benign lesion, it is considered more suitable.